Association between the homeostasis model assessment of insulin resistance and coronary artery calcification: a meta-analysis of observational studies - Li, Longti; Zhong, Huiqin; Shao, Ya; Hua, Yu; Zhou, Xu; Luo, Desheng (Frontiers in Endocrinology, 2023)
Background Insulin resistance (IR), a risk factor for cardiovascular diseases, has garnered significant attention in scientific research. Several studies have investigated the correlation between IR and coronary artery calcification (CAC), yielding varying results. In light of this, we conducted a systematic review to investigate the association between IR as evaluated by the homeostasis model assessment (HOMA-IR) and CAC. Methods A comprehensive search was conducted to identify relevant studies in PubMed, Embase, Scopus, and Web of Science databases. In addition, preprint servers such as Research Square, BioRxiv, and MedRxiv were manually searched. The collected data were analyzed using either fixed or random effects models, depending on the heterogeneity observed among the studies. The assessment of the body of evidence was performed using the GRADE approach to determine its quality. Results The current research incorporated 15 studies with 60,649 subjects. The analysis revealed that a higher category of HOMA-IR was associated with a greater prevalence of CAC in comparison to the lowest HOMA-IR category, with an OR of 1.13 (95% CI: 1.06–1.20, I2 = 29%, P < 0.001). A similar result was reached when HOMA-IR was analyzed as a continuous variable (OR: 1.27, 95% CI: 1.14–1.41, I2 = 54%, P < 0.001). In terms of CAC progression, a pooled analysis of two cohort studies disclosed a significant association between increased HOMA-IR levels and CAC progression, with an OR of 1.44 (95% CI: 1.04–2.01, I2 = 21%, P < 0.05). It is important to note that the strength of the evidence was rated as low for the prevalence of CAC and very low for the progression of CAC. Conclusion There is evidence to suggest that a relatively high HOMA-IR may be linked with an increased prevalence and progression of CAC.